Angiosperm flora of Rampahar Reserve Forest under Rangamati district in Bangladesh. I. Liliopsida (Monocots) (Bangladesh Journal of Plant Taxonomy, 2012)
A systematic floristic study of Rampahar reserve forest under Rangamati district in Bangladesh has revealed 89 monocot (Liliopsida) taxa belonging to 66 genera under 15 families. Out of these recorded taxa, 73 are herbs, 9 climbers, 3 bamboos, 3 reeds and 1 tree species. The area harbours 11 threatened species of the country. Updated nomenclature with full reference citation, habit and representative specimen have been provided for each species. Well known synonyms and local name(s) have also been given in some cases.DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10940Bangladesh J. Plant Taxon. 19(1): 37-44, 2012 (June)